Management of severe dengue in children. - Moxon, C; Wills, B (2008)
Dengue is a major global disease which, in its severe form, affects up to 500,000 people worldwide each year, most of whom are children. The development of a safe and effective vaccine is a clear priority, together with public health measures to prevent the spread of infection. However, while major epidemics continue to occur, clinicians must also focus on optimising management. Although no specific treatment is available at present, with good supportive care, mortality for children with DHF can be reduced to well below 1%. In patients without signs of shock, fluid replacement can be attempted orally, but in children with DSS parenteral treatment is essential. Very careful titration of fluid therapy is necessary combined with frequent reassessment for signs of worsening shock or the development of fluid overload. In most DSS cases isotonic crystalloid solutions are as effective as colloid solutions, but the question whether early intervention with colloid solutions improves outcome in more advanced shock requires further investigation. The outcome of studies to address this question, together with further research to examine the pathophysiological mechanisms underlying the plasma leakage, will hopefully result in better management of children with severe dengue but may also provide useful insights into other diseases that affect endothelial function.